2011
DOI: 10.5688/ajpe759175
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Student Impact on Inappropriate Prescribing of Acid Suppressive Therapy

Abstract: Objective. To examine the impact that having pharmacy students on internal medicine patient care teams had on inappropriate prescribing of acid suppressive therapy (AST). Methods. In this observational cohort study, internal medicine patients who received care from teams with a pharmacy student were compared to patients who received care from teams without a pharmacy student. The primary endpoint was proportion of patients on inappropriate AST. Results. The overall proportion of patients receiving inappropriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(36 citation statements)
references
References 10 publications
0
36
0
Order By: Relevance
“…The PRISMA flowchart of study inclusion is illustrated in Fig 1 [55]. After screening and determination of eligibility of 14,422 citations, 17 articles published between 2007 and 2019 were ultimately included in the meta-analysis [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79]. These 17 publications resulted in 16 studies since Buckley et al [65] reported data for both the ICU and non-ICU settings in a single publication and two authors published results of pre-and post-intervention data in separate articles; in the ICU setting: Wohlt et al (pre-implementation) [75] and Hatch et al (post-implementation) [68]; in the non-ICU setting: Khudair et al (pre-implementation) [71] and Khudair et al (post-implementation) [70].…”
Section: Study Inclusionmentioning
confidence: 99%
See 3 more Smart Citations
“…The PRISMA flowchart of study inclusion is illustrated in Fig 1 [55]. After screening and determination of eligibility of 14,422 citations, 17 articles published between 2007 and 2019 were ultimately included in the meta-analysis [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79]. These 17 publications resulted in 16 studies since Buckley et al [65] reported data for both the ICU and non-ICU settings in a single publication and two authors published results of pre-and post-intervention data in separate articles; in the ICU setting: Wohlt et al (pre-implementation) [75] and Hatch et al (post-implementation) [68]; in the non-ICU setting: Khudair et al (pre-implementation) [71] and Khudair et al (post-implementation) [70].…”
Section: Study Inclusionmentioning
confidence: 99%
“…Sample [70,71]; Carey et al collected three months of data during the no-pharmacy-student period versus pharmacy-student period [66] and Van der Linden et al collected eleven months of data for the control group (RASP list applied retrospectively) versus intervention group (RASP list applied by pharmacist prospectively) [79]. In studies that provided data [64,65,70,71,79], patients' mean age ranged from 51 to 84.5 years and percentage of males ranged from 44% to 81%.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has demonstrated the impact of student pharmacists in acute care settings through clinical interventions and recommendations. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] In these studies, students delivered recommendations through activities including chart review, rounds, and other pharmaceutical care programs; medication reconciliation was not a service students were typically engaged in. Lubowski et al 15 did specifically look at the impact of students delivering medication reconciliation in a community hospital and found that students were able to identify and resolve drug-related problems.…”
Section: Introductionmentioning
confidence: 99%